Організаційно-економічні засади створення інноваційно-інтегрованих структур в умовах соціально-економічної нестабільності - Левченко, О. М.; Ткачук, О. В.; Левченко, А. Н.; Levchenko, О.; Tkachuk, О. (ЦНТУ, 2018)
Статья посвящена обоснованию организационно-экономических основ создания инновационно-интегрированных структур в условиях социально-экономической нестабильности на основании анализа текущего состояния показателей конкурентоспособности и инновационного развития Украины на международной арене и мировых тенденций инновационной динамики. Охарактеризованы предпосылки, факторы, принципы, составляющие и задачи развития инновационно-интегрированных объединений. Обоснована целесообразность учета основных составляющих формирования и развития инновационно-интегрированных структур. Статья посвящена обоснованию организационно-экономических основ создания инновационно-интегрированных структур в условиях социально-экономической нестабильности на основании анализа текущего состояния показателей конкурентоспособности и инновационного развития Украины на международной арене и мировых тенденций инновационной динамики. Охарактеризованы предпосылки, факторы, принципы, составляющие и задачи развития инновационно-интегрированных объединений. Обоснована целесообразность учета основных составляющих формирования и развития инновационно-интегрированных структур. The article is devoted to the substantiation of the organizational and economic principles of creation of innovative-integrated structures in the conditions of socio-economic instability on the basis of the results of the analysis of the current state of competitiveness's indicators and innovative development of Ukraine in the international arena and world tendencies of innovation dynamics. The comparative characteristic of the key indicators of innovative development in Ukraine with the individual countries of the world, are made it possible to ascertain both significant negative socioeconomic processes and a fairly significant level of lagging behind the key indicators of innovative development from countries of the world, which are showing the high rates of innovative dynamics or are at the stage of growth. The preconditions, factors, principles, components and tasks of development of innovative-integrated associations were characterized. The expediency of taking into account the main components of the forming and development of innovative-integrated structures, including the educational component of training specialists for innovative-integrated structures (quality, competitiveness of educational services, financing, scientific activity of educational institutions); professional development of employees of innovative-integrated structures (lifelong learning, increasing of human capital); personnel support (availability of innovative type of personnel, innovative development of human capital); directions of improvement of the organizational and regulatory influence in the conditions of decentralization of power and management (development of strategies, territorial priorities, transparency of public procurement, implementation of program-targeted approach); financial analysis, audit and information support (financial information, audit services, currency rate regulation, information requirements); tax regulation (advantages and disadvantages of the taxation system, tax incentives); investment support (state financial support, investment attractiveness of enterprises); stimulation of entrepreneurial activity (problems and prospects of development of innovative entrepreneurship); social development (development of social capital); ensuring national security (the role of innovative-integrated structures) was substantiated. Thus, the improvement of the organizational-economic principles for the creation of innovative-integrated structures should take into account the latest trends associated with the results of the 4th industrial revolution, the peculiarities of implementing innovative activities in conditions of socio-economic instability, must be oriented towards the formation of innovative ecosystems, introduction of a smart approach to management organization, territorial branding, enhancement of the competitiveness of the territories and their investment attractiveness.
Организационно-экономические основы создания инновационно-интегрированных структур в условиях социально-экономической нестабильности
The Organizational-Economic Principles of Creation of Innovative-Integrated Structures in Conditions of Socio-Economic Instability
Keywords: инновационно-интегрированная структура; социально-экономическая нестабильность; четвертая промышленная революция; кластеризация; конкурентоспособность; инновационное развитие; инновационно-интегрированная структура; инновационное развитие; конкурентоспособность; кластеризация; четвертая промышленная революция; социально-экономическая нестабильность; innovative-integrated structure; innovation development; competitiveness; clusterization; the 4th industrial revolution; socio-economic instability